EFEKTIVITAS REMEDIASI BERBENTUK PENYEDIAAN REFUTAXION TEXT PADA MATERI ATOM, MOLEKUL, DAN ION DI SMK - Fitri Kusuma Wardani; Hairida Hairida; Rody Putra Sartika (Universitas Tanjungpura, 2019)
AbstractThe purpose of this study was to determine the improvement of student learning outcomes before and after remediation in the form of provision of refutation text in atoms, molecules, and ions, and to describe the effectiveness of remediation in form of in understanding atoms, molecules, and ions in students class X SMK PGRI Pontianak. This research was in the form of a quasi-experimental design model “one group pretest-posttest design”. The subject of the study consisted of 46 students spread over X TAV, X TSM, and X TKJ classes. The data collection test consisting of a preliminary test and a multiple choice final test with three alternative answer with reasons. The results showed that there was a decrease in the average student’s misconception of atoms, molecules, and ions by 34,76%. This show an increase in student learning outcomes before and after remediation in the form of providing refutation text. In addition, an effect size of 4,4 was obtained. This showed that remediation with refutation text was generally effective in reducing student misconceptions. Keywords: Effectiveness, refutation text, remediation